(untitled) (Journal of Medical & Health Sciences Review, 2025)
Chronic hepatitis B virus (HBV) infection is a leading cause of cirrhosis and portal hypertension worldwide, affecting approximately 296 million people and causing nearly 1 million deaths annually from complications. Hepatitis D virus (HDV) co-infection occurs in 5% of HBV carriers. This study aimed to compare the frequency of esophageal varices in HBV-monoinfected patients versus those co-infected with HDV. A cross-sectional study was conducted at a tertiary care hospital in Sukkur, Pakistan over 6 months. A total of 132 patients with chronic HBV infection (≥3 months, age 20–80, both sexes) were enrolled consecutively. HDV serology (anti-HDV ELISA) was performed to categorize patients into HBV-only or HBV+HDV groups. All patients underwent clinical evaluation and laboratory workup; upper gastrointestinal endoscopy was then performed by an experienced gastroenterologist (blinded to HDV status). Statistical analysis was done with SPSS v26. Continuous variables were assessed for normality using the Shapiro-Wilk test. A multivariable logistic regression was performed to estimate the association of HDV co-infection with presence of varices. These findings suggest that HDV co-infection contributes to variceal development primarily by increasing the likelihood of advanced liver disease (cirrhosis). In this cohort of chronic hepatitis B patients, concomitant HDV infection was associated with a significantly higher frequency of esophageal varices.